2010
DOI: 10.1038/labinvest.2010.61
|View full text |Cite
|
Sign up to set email alerts
|

The role of osteopontin and tumor necrosis factor alpha receptor-1 in xenobiotic-induced cholangitis and biliary fibrosis in mice

Abstract: Background & Aims Proinflammatory and profibrotic cytokines such as osteopontin (OPN) and tumor necrosis factor-alpha receptor 1 (TNFR1) may be critically involved in the pathogenesis of cholangiopathies and biliary fibrosis. We therefore aimed to determine the role of genetic loss of either OPN or TNFR1 in 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC)-fed mice as a model of xenobiotic-induced sclerosing cholangitis with biliary-type liver fibrosis using respective knock-out mice. Methods OPN and TNFR1 kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 52 publications
1
36
0
Order By: Relevance
“…Work by Fickert et al 43 suggested that genetic loss of Opn in mice on C57BL/6J background only did not affect the pathogenesis of the 3,5-diethoxycarbonyl-1,4-dihydrocollidine model of sclerosing cholangitis and biliary-type liver fibrosis. Their conclusions were based solely on the presence of CK19 + cells as a readout for DR since no studies were performed to dissect how DR could regulate the profibrogenic potential of HSC and/or portal fibroblasts 43. Yet, the authors indicated that their experimental findings did not allow the direct conclusion that OPN has no role in biliary fibrosis induced under different experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work by Fickert et al 43 suggested that genetic loss of Opn in mice on C57BL/6J background only did not affect the pathogenesis of the 3,5-diethoxycarbonyl-1,4-dihydrocollidine model of sclerosing cholangitis and biliary-type liver fibrosis. Their conclusions were based solely on the presence of CK19 + cells as a readout for DR since no studies were performed to dissect how DR could regulate the profibrogenic potential of HSC and/or portal fibroblasts 43. Yet, the authors indicated that their experimental findings did not allow the direct conclusion that OPN has no role in biliary fibrosis induced under different experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, several groups have studied the potential role of OPN induction in liver fibrosis albeit with conflicting results 17–19 42 43. Work by Fickert et al 43 suggested that genetic loss of Opn in mice on C57BL/6J background only did not affect the pathogenesis of the 3,5-diethoxycarbonyl-1,4-dihydrocollidine model of sclerosing cholangitis and biliary-type liver fibrosis. Their conclusions were based solely on the presence of CK19 + cells as a readout for DR since no studies were performed to dissect how DR could regulate the profibrogenic potential of HSC and/or portal fibroblasts 43.…”
Section: Discussionmentioning
confidence: 99%
“…This type of progressive biliary injury is initially characterized by specific transporter abnormalities, involving canalicular expression of Sodium/Taurocholate Cotransporter (Ntcp), organic anion transporting polypeptide (Oatp4), and Multidrug Resistance-Associated Protein 2 (Mrp2), responsible for reduced biliary excretion of glutathione (GSH) and phospholipids, occurring before phenotypic changes of cholangiocytes (‘reactive cholangiocyte’) [19]. Reactive cholangiocytes show increased expression of profibrogenic and proinflammatory cytokines, including osteopontin and tumor necrosis factor-alpha (TNF-α), associated with infiltration of neutrophils, and then with activation of periductal myofibroblasts, around both large and small bile ducts [21]. Recent morphological evidence showed that DDC-induced liver injury also leads to hepatocellular necrosis and, consequently, activation of Kupffer cells and compensatory hepatocyte proliferation [2224].…”
Section: 35-diethoxycarbonyl-14-dihydrocollidine (Ddc)mentioning
confidence: 99%
“…1C), onionskin-type periductal fibrosis, and finally biliary fibrosis, therewith reflecting several specific pathological hallmarks of human PSC (42). This model is therefore especially useful to investigate the mechanisms of chronic cholangiopathies and their consequences, including biliary fibrosis, and to test novel therapeutic approaches for these diseases (42,43).…”
Section: Animal Models Of Pscmentioning
confidence: 99%